The Management of Elderly Prisoners in France. (November 2019) - Combalbert, Nicolas; Rambourg, Cecile
Very few studies have examined the mental disorders of elderly prisoners and the difficulties related to their management. For this study, 40 prison workers were interviewed (custodial staff, social workers, and probation officers) to assess staff professional practices and approaches in managing elderly inmates. Findings showed highly ambivalent attitudes to the age-related vulnerabilities of elderly incarcerees, at both emotional and professional levels. Staff attempts to make the incarcerated elderly conform to some four traditional images of the prisoner roles (enemy/citizen/threat/user) may lead some prison staff to use emotional defense mechanisms.